Line managers in industrial relations: Where are we now and where to next?. (April 2017) - Townsend, Keith; Hutchinson, Sue
Interactions between line managers and subordinate employees are fundamental to the employment relationship and, therefore, to industrial relations as a field of both study and practice. Human resource management literature has focused on the responsibilities line managers have as implementers of employment policy and practice, for example in dealing with grievance and disciplinary matters, communication and involvement, the application of discrimination policies, and the management of pay. Thus, it is surprising that this body of managers has been neglected in recent industrial relations research. This article fits the theme of the special issue by providing an overview of 'where we are' and sets out a research agenda of 'Where to next?', for the study of line managers in industrial relations research.